µ-Patterning of Carbon Nanotube patterning of Carbon Nanotube (CNT) forest for MEMS applications - Saleh, Tanveer (2013)

(untitled)
This paper proposes three new approaches for micro patterning of CNT forest in order to make it useful for MEMS based applications. The first two techniques are based on micro electro discharge machining (-EDM). However, the biggest problem associated with EDM is the spark gap which limits the structural resolution of the fabricated pattern. In order to overcome this challenge the first technique proposed in this paper is reverse EDMing of CNT forest where the CNTs are used as cathode instead of tungsten tool. This dramatically reduces discharge voltage hence the spark gap. In the second method Sulphur Hexafluoride (SF6) SF6 was used as dielectric instead of air which has three time higher dielectric strength than air. This helps to reduce spark gap further. This research work also discusses the experimental results when SF6 was used as dielectric medium for reverse EDMing CNT forest. It was observed that at too low voltage (~10V) air gives lower spark gap than SF6, however at moderately high voltage (~25V) SF6 performs better. Finally, the third approach for patterning CNT forest described in this paper is mechanical bending of CNTs. In this method patterning of CNT forest is carried out by moving a rotating cylindrical tool (3000RPM) in X,Y and Z direction. The Z movement of the tool is controlled in step mode to provide the overall depth of the structures with 1m/step. In XY plane the tool moves continuously at 1mm/min speed. The movement of the tool on the CNT forest causes the CNTs to be bent and flattened in the direction of the tool motion hence the patterns are formed on bare CNT forest. The most significant observation made from the processed CNT forest is the visible optical reflection from bent and flattened area. Typically, CNT forest is known to be the darkest material on earth. However, this new processing technique causes the CNT surface to reflect light like mirror. A detail comparison between all proposed techniques (mechanical and reverse EDM) for patterning CNT forest is also included in this paper.